Assessing the Effect of Preoperative Nutrition on Upper Body Function in Elderly Patients Undergoing Elective Abdominal Surgery. Issue 3 (12th December 2017) - Sikder, Tarifin; Maimon, Geva; Sourial, Nadia; Tahiri, Mehdi; Teasdale, Debby; Bernier, Paule; Fraser, Shannon A.; Demyttenaere, Sebastian; Bergman, Simon
Abstract: Background : Malnutrition among elderly surgical patients has been associated with poor postoperative outcomes and reduced functional status. Although previous studies have shown that nutrition contributes to patient outcomes, its long‐term impact on functional status requires better characterization. This study examines the effect of nutrition on postoperative upper body function over time in elderly patients undergoing elective surgery. Methods : This is a 2‐year prospective study of elderly patients (≥70 years) undergoing elective abdominal surgery. Preoperative nutrition status was determined with the Subjective Global Assessment (SGA). The primary outcome was handgrip strength (HGS) at 1, 4, 12, and 24 weeks postsurgery. Repeated measures analysis was used to determine whether SGA status affects the trajectory of postoperative HGS. Results : The cohort included 144 patients with a mean age of 77.8 ± 5.0 years and a mean body mass index of 27.7 ± 5.1 kg/m 2 . The median (interquartile range) Charlson Comorbidity Index was 3 (2–6). Participants were categorized as well‐nourished (86%) and mildly to moderately malnourished (14%), with mean preoperative HGS of 25.8 ± 9.2 kg and 19.6 ± 7.0 kg, respectively. At 24 weeks, 64% of well‐nourished patients had recovered to baseline HGS, compared with 44% of mildly to moderately malnourished patients. Controlling for relevant covariates, SGA did not significantly affect the trajectory of postoperative HGS. Conclusion : While HGS values over the 24 weeks were consistently higher in the well‐nourished SGA group than the mildly to moderately malnourished SGA group, no difference in the trajectories of HGS was detected between the groups.